Uncovering below cloud rain‐vapor interactions during tropical rain events through simultaneous and continuous real‐time monitoring of rain and vapor isotopes - He, Shaoneng (2025)
Due to limited water vapor measurements, vapor isotopes have been traditionally estimated under the assumption of isotopic equilibrium between rain and vapor below cloud base. However, recent advancements in analytical instruments allow more vapor isotopic measurements that have challenged this assumption. To enhance our understanding of rain-vapor interactions below cloud base in tropical regions, we established an automated system to measure rain and vapor isotopes simultaneously and continuously in real time at minute intervals in Singapore. Among 324 rain events monitored from 2016 to 2019, 81% exhibited a substantial departure of rain and vapor isotopes from the expected equilibrium. This departure suggests that raindrop evaporation plays a larger role in determining their isotopes. The conclusion is supported by the generally lower slopes of the local meteoric water line. Seasonal variations in rain event characteristics indicate changing influences of rain-vapor interactions: during monsoons, more frequent heavy rainfall maintains relatively high humidity below cloud base, favoring rain-vapor isotopic equilibrium, whereas during inter-monsoons, more light rain events lead to pronounced rain evaporation and larger isotopic differences. Furthermore, rain-vapor interactions below cloud base significantly modulated their isotope evolution during individual events. As events progressed, reduced humidity favored evaporation, increasing rain isotope values and decreasing its d-excess, whereas vapor isotope values decreased and its d-excess increased. Our study introduces a new approach to capturing real-time high-resolution rain and vapor isotopes at minute intervals to understand the dynamics of rain-vapor interactions below cloud base. Findings underscore the crucial role of these interactions in influencing rain and vapor isotopes during tropical rain events.